BORON INCREASES THE GROWTH AND YIELD OF MUNGBEAN - Ali, Muhammad Asghar (JOURNAL OF ADVANCES IN AGRICULTURE, 2016)
Pulses have significant role in the profitability of agriculture because of major proportion of our population depends on it due to its higher nutritional value, rich source of protein and low price. Pulses are also important component of animal feed and their dried straw is used as hay. In pulses, mungbean (Vigna radiata L.) is a vital crop. Boron has positive effect on growth and development, nitrogen assimilation and root growth. Low level of boron causes negative impact on growth, narrow leave expansion, restricted root elongation and morphological features of mungbean plant.